Bibliometric and visualization analysis of radiation brain injury from 2003 to 2023 - Wu, Baofang; Li, Shaojie; Wang, Jian; Wang, Jiayin; Qiu, Weizhi; Gao, Hongzhi (Frontiers in Neurology, 2024)
Background Over the past two decades, the field of radiation brain injury has attracted the attention of an increasing number of brain scientists, particularly in the areas of molecular pathology and therapeutic approaches. Characterizing global collaboration networks and mapping development trends over the past 20 years is essential. Objective The aim of this paper is to examine significant issues and future directions while shedding light on collaboration and research status in the field of radiation brain injury. Methods Bibliometric studies were performed using CiteSpaceR-bibliometrix and VOSviewer software on papers regarding radiation brain injury that were published before November 2023 in the Web of Science Core Collection. Results In the final analysis, we found 4,913 records written in 1,219 publications by 21,529 authors from 5,007 institutions in 75 countries. There was a noticeable increase in publications in 2014 and 2021. The majority of records listed were produced by China, the United States, and other high-income countries. The largest nodes in each cluster of the collaboration network were Sun Yat-sen University, University of California–San Francisco, and the University of Toronto. Galldiks N, Barnett GH, Langen KJ and Kim JH are known to be core authors in the field. The top 3 keywords in that time frame are radiation, radiation necrosis, and radiation-therapy. Conclusions The objective and thorough bibliometric analysis also identifies current research hotspots and potential future paths, providing a retrospective perspective on RBI and offering useful advice to researchers choosing research topics. Future development directions include the integration of multi-omics methodologies and novel imaging techniques to improve RBI's diagnostic effectiveness and the search for new therapeutic targets.